Engineering mathematics:for 1st year 1st semester all stream - Pal,B.K (U.N.Dhur & Sons, 2018)
Engineering mathematics:for 1st year 1st semester all stream / Pal,B.K. -- Kolkata: U.N.Dhur & Sons, 2018 510 P153e10V1 10th ed No. of Copies : 1